Peran Komunikasi Interpersonal dalam Memelihara Keharmonisan Lintas Suku di Kelurahan Bandar Selamat Kecamatan Medan Tembung - Zulham; Hasan Sazali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Abstract This research aims to find out how the role of interpersonal communication in maintaining inter-ethnic harmony in Bandar Selamat Village, Medan Tembung Sub-district. This research uses a descriptive qualitative approach sourced from interviews, observations, and documentation then uses Joseph A Devito's interpersonal communication theory. The selection of informants using purposive sampling technique is as many as 7 informants. The results showed that interpersonal communication has an important role in maintaining cross-ethnic harmony. How to maintain cross-ethnic harmony by conducting gatherings and greeting each other between cross-ethnic communities. The application of interpersonal communication has been effective based on Devito's interpersonal communication theory. The obstacles are age differences and the language used daily. Keywords: Intertribal Harmony, Interpersonal Communication, Medan Tembung.